Constructing Male Immaturity through Figurative Language: A Stylistic Analysis of Sabrina Carpenter’s “Manchild” - Yasin Ali Rogas; Ristati Ristati; Dellis Pratika (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines how figurative language constructs male immaturity in Sabrina Carpenter’s Manchild. The song was selected because it has attracted widespread public attention for its critical portrayal of male behavior through rich figurative expressions, making it an appropriate text for stylistic analysis. Using a qualitative descriptive design, the study applies Perrine’s and Rozakis’ classifications of figurative language alongside Leech and Short’s stylistic theory to analyze both the types and functions of figurative expressions. The data consist of lyric lines collected through documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that irony is the dominant device (36.8%), followed by hyperbole (31.6%) and sarcasm (15.8%), while metaphor, paradox, and ambiguity occur less frequently. Rather than functioning independently, these devices interact to construct a critical representation of male immaturity. Irony serves as the primary evaluative strategy, whereas hyperbole and sarcasm intensify criticism through exaggeration and ridicule. This study contributes to stylistic and linguistic research by integrating figurative language classification with functional analysis and demonstrating how figurative language constructs gendered meaning and social criticism in contemporary popular music.